Fiscal Policy Rules for Stabilisation and Growth : A Simulation Analysis of Deficit and Expenditure Targets in a Monetary Union - Tilman Brück; Rudolf Zwiener (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
We analyse the effectiveness of fiscal policy rules for business cycle stabilisation in a monetary union using a quarterly macro-econometric model of Germany. The simulations compare a deficit target and an expenditure target under a range of supply, demand and fiscal shocks. Their effects are evaluated by their impact on prices and output. The analysis demonstrates that in general the deficit target of the stability pact leads to less stabilisation than an expenditure target. The results suggest that the deficit rule of the stability pact should be replaced with an expenditure rule augmented by medium-term debt targets.
Keywords: F42; E62; E37; 330; fiscal policy; international policy coordination; simulation; Antizyklische Finanzpolitik; EU-Stabilitätspakt; Währungsunion; Wirtschaftspolitische Wirkungsanalyse; Simulation; Haushaltsdefizit; Öffentliche Ausgaben; Schätzung; Deutschland